Quality of Life of Nurses and Related Factors - Zahra Omrani; Elnaz Talebi (Shahrekord University of Medical Sciences, 2018)
Background and aims: A high number of healthcare team members are nurses. Nurses' quality of life level is an important issue because it affects their level of care delivered to their patients. Knowledge about nurses' level of quality of life is useful for planning. The present study was conducted to examine the quality of life of nurses and related factors. Methods: This cross-sectional descriptive study was performed during 2015-2016. Samples were recruited from single nurses who worked in teaching hospitals in Tehran. To this end, 200 nurses were selected by using simple random sampling method. Data collection was performed by researchers using a researcher's self-designed checklist for demographic characteristics and a 36-Item Short Form Survey (SF-36). After data collection, data analysis was performed using SPSS 19.0 software. Results: Of 200 nurses, 118 (59%) were female, and 82 (41%) were male. Of 200 nurses, 192 (96%) were registered nurses and the rest had Master of Science degree in nursing. The mean score of quality of life was 71.44±10.12. Among subscales of quality of life, higher and lower scores were related to the subscale 'social role functioning' and 'physical functioning', respectively. Nurses' sex was a significant factor that affected their quality of life (P<0.05). Conclusion: According to the findings of the present study, nurses' quality of life was at moderate level totally; however in some subscales they had some problems. Nurses' quality of life needs more attention. Further study in this regard is recommended.